2018
DOI: 10.1016/j.lungcan.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Is heterogeneity in stage 3 non-small cell lung cancer obscuring the potential benefits of dose-escalated concurrent chemo-radiotherapy in clinical trials?

Abstract: The current standard of care for the management of inoperable stage 3 non-small cell lung cancer (NSCLC) is concurrent chemoradiotherapy (cCRT) using radiotherapy dose-fractionation and chemotherapy regimens that were established 3 decades ago. In an attempt to improve the chances of long-term control from cCRT, dose-escalation of the radiotherapy dose was assessed in the RTOG 0617 randomised control study comparing the standard 60 Gy in 30 fractions with a high-dose arm receiving 74 Gy in 37 fractions. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…A retrospective analysis utilizing National Cancer Data Base enrolled 33,566 patients with stage III NSCLC treated by thoracic radiation, and the results showed that patients with dose of ≥66Gy had increased OS than those with dose of 59.4-60Gy (median: 21.1 vs 18.8 months) [18]. Dose-escalation is still a feasible tool to improve outcome if the toxicity can be well controlled [19]. SIB-IMRT seems to be a useful technique for dose-escalation, in which the increased dose was only delivered to GTV/PGTV [20].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis utilizing National Cancer Data Base enrolled 33,566 patients with stage III NSCLC treated by thoracic radiation, and the results showed that patients with dose of ≥66Gy had increased OS than those with dose of 59.4-60Gy (median: 21.1 vs 18.8 months) [18]. Dose-escalation is still a feasible tool to improve outcome if the toxicity can be well controlled [19]. SIB-IMRT seems to be a useful technique for dose-escalation, in which the increased dose was only delivered to GTV/PGTV [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a true person-centred approach is lacking in this research, with the majority of studies and proposals aiming to simply escalate dose without a focus on the patient characteristics. A recent publication [39] highlights the vast heterogeneity within this population and the myriad of factors that are not yet considered in our treatment approach. This may well provide a starting point for improved patient stratification and thus personalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating these potential advances with recent developments in disease staging, diagnostic imaging and molecular profiling could create comprehensive investigational strategies to improve outcomes in future stage III NSCLC clinical trials. [44][45][46][47][48][49] ADJUVANT IMMUNOTHERAPY AFTER CONCURRENT CHEMORADIOTHERAPY IN STAGE III NSCLC The synergistic effect between radiation and immune-checkpoint modulations has been demonstrated in multiple preclinical studies, [50][51][52][53][54][55][56][57] and more recently in the clinical setting following the publication of the Phase 3 PACIFIC trial results. 49 The use of immune-checkpoint antagonists, specifically anti-PD-1 and anti-PD-L1 therapeutics, has resulted in improved OS in patients with metastatic lung cancer, and has transformed the therapeutic landscape in the first-58 and second-line treatment settings.…”
Section: Optimal Chemotherapy Regimens and Radiotherapy Dose Fractionmentioning
confidence: 99%